Ablalesmya Johannsen, 1905 Neotropicais (Diptera, Chironomidae, Tanypodinae) : uma abordagem morfológica e molecular - Oliveira, Caroline Silva Neubern de (2011)
Orientador : Prof. Dr. Mário A. Navarro Silva